2022
DOI: 10.3390/molecules27238353
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the Future Pandemics: Broad-Spectrum Antiviral Agents (BSAAs) Based on A-Type Proanthocyanidins

Abstract: A-type proanthocyanidins (PAC-As) are plant-derived natural polyphenols that occur as oligomers or polymers of flavan-3-ol monomers, such as (+)-catechin and (−)-epicatechin, connected through an unusual double A linkage. PAC-As are present in leaves, seeds, flowers, bark, and fruits of many plants, and are thought to exert protective natural roles against microbial pathogens, insects, and herbivores. Consequently, when tested in isolation, PAC-As have shown several biological effects, through antioxidant, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 285 publications
1
9
0
Order By: Relevance
“…We should initiate comprehensive drug discovery programs for viruses that have pandemic potential, focusing on prototype pathogens. These approaches should prioritize drugs that act broadly against such virus families to provide protection against novel viruses that emerge, so they are poised to be trialed in infected patients when the next pandemic emerges [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We should initiate comprehensive drug discovery programs for viruses that have pandemic potential, focusing on prototype pathogens. These approaches should prioritize drugs that act broadly against such virus families to provide protection against novel viruses that emerge, so they are poised to be trialed in infected patients when the next pandemic emerges [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these results indicated that A18 was able to inhibit the expression of some critical viral proteins and the viral RNA synthesis in the context of different virus infections. The antiviral action of several anthocyanidins has been associated with the inhibition of the virus adsorption to the cell surface [2]. Therefore, we decided to analyze whether A18 exerts its broad-spectrum antiviral activity through this mechanism of action.…”
Section: Broad-spectrum Antiviral Activity Of A18mentioning
confidence: 99%
See 3 more Smart Citations